IDEALISME TATA EKONOMI INDONESIA PASCA PEMERINTAHAN SBY-JK - Widayat, Widayat (Jurnal Bestari, 2009)
Economic development performance of Indonesia had regarded mainstream that it was interesting topic before presidential ellection in 2009. Liberalism and pro the poor are words  that appeared strongly at that time. Indeed, it had become a controversy of related topic which was suitable for developing Indonesian's economy. They have advantages and also disadvantages. Morever, Indonesia has special characteristics.